PENERAPAN IPTEK PADA USAHA KUE KERING DESA BUGO KABUPATEN JEPARA - Saptariana, Saptariana; Agustina, Titin; S., Hanna Lestari (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
Partners IbM devotion is home industry pastries â€œSri Jayaâ€ and â€œFlavor of Loveâ€ which produces pastries, pia and bread. The problems that arise are: (1) aspects of production where tool to smooth the stuffing in the form of green beans kumbu using a mortar pestle. In addition to cooking kumbu, the tool used is steamed and pan large, (2) the quality aspects of pastries and pia generated needs to be improved to expand marketing, (3) aspects hiegene and sanitation, (4) aspects of business management and marketing. Pursuant to the problems faced by partner activities of science and technology for society (IbM) above, then the solutions offered are: (1) Applied two units grinder to smooth kumbu green beans, (2) be applicable two units of pressure cooker to cook green beans in order to quickly padded, (3) Produced recipe pastries and pia with good quality that can be accepted by consumers at large, (4) Given the results of organoleptic test: in terms of taste, color, aroma and texture as well as known results of testing consumer preferences, (5) Resulting design and the packaging quality pastries and pia more interesting, (6) Given the nutritional content such as: carbohydrates, fat, protein, moisture and ash content, (7) business management (accounting and administration) recorded a complete and tidy, (8) Marketing using brochures and online, (9) Advantage partner increases, (10) Resulting scientific articles in national journals.